Tích hợp nội dung giáo dục địa phương trong dạy học môn Lịch sử và Địa lí lớp 4 tại phường Việt Trì, tỉnh Phú Thọ - Đinh Thị Nguyệt, Linh; Nguyễn Hoàng, Hoàng Linh; Nguyễn Thị Hải, Hà (Tạp chí Giáo dục, 2026)
In the context of implementing Vietnam’s 2018 General Education Curriculum, integrating local education content into Grade 4 History and Geography teaching plays an important role in connecting classroom knowledge with real-life contexts and developing students’ competencies. Employing a mixed-methods design that combined document analysis, questionnaire surveys of 45 teachers and 150 students, classroom observations, and interviews, this study examined opportunities for integrating local education content into Grade 4 History and Geography, investigated current practices at several primary schools in Viet Tri Ward, Phu Tho Province, and proposed relevant measures. The findings indicate that teachers mainly relied on lectures supported by visual illustrations (75.6%), whereas experiential activities and project-based learning were implemented less frequently. Students performed relatively well in recalling local knowledge, with 68.0% achieving a good level, but showed limitations in analysis and application. In addition, 78% of the teachers reported difficulties in accessing and using digital teaching resources. Based on these findings, the study proposes measures to support teachers in integrating local education content into Grade 4 History and Geography teaching in line with the competency- and quality-oriented approach of the 2018 General Education Curriculum.